16.0k views
5 votes
Evaluate the expression. 7+4×9-6÷3

User Laher
by
5.4k points

2 Answers

4 votes

The answer is 41

That is the answer because first you would do 4x9 which equals 36. Then you would do 6 divided by 3 which equals 2. Then you would do 7+36-2 and 7+36 equals 43 and 43 minus 2 equals 41.


Just remember how to do it in order by doing this

G = grouping symbols

E= exponents

M= multiplication ( for multiplication and division the one that is first goes first)

D= division

A= addition ( for addition and subtraction the one that is first is first)

S= subtraction


User Trajan
by
5.7k points
7 votes

7+4x9-6/3


pemdas:

7+36-2

43-2

41

User Violet Giraffe
by
5.4k points